THE HABIT OF CURIOSITY - CARLA CESARE (Agathos: An International Review of the Humanities and Social Sciences, 2014)
Curiosity is commonly referred to as a way of being, or an object of curiosity. How curiosity is part of our daily lives, how we engage with curiosity intellectually has a long and interesting history. Since the sixteenth century it has been manifest in cabinets of curiosity, museums and curio cabinets; exercises in collecting, self-reflection and discovery. However, the end of the twentieth-century has altered our sense of the world, through the speed and accessibility of information leaving a changed relationship with wonder. This paper discusses the role of curiosity in research as a “habit of curiosity”, (Benedict 2001, 2) a method for discovery. It reviews its historical manifestations and concerns, locating it through objects and actions, and questions what new meanings the twenty-first century brings with it. Is curiosity at risk? Is it still risky? The relationship between the individual and their interior and exterior socio-cultural landscape continually creates new meanings for knowledge and how we achieve it. This shadowy landscape of our curiosity has not lost meaning intellectually, but it in our shrinking, globalized world how we engage with it requires a new investigation.